Die grosse Edgar Wallace Krimi-Collection - Wallace, Edgar 1875-1932; Wallace, Edgar 1875-1932 (The Edgar Wallace Mysteries, 2024)
A publisher is nearly framed for murder, but he appears to have been goaded by the blackmailer who has also blackmailed the publisher's wife. [www.imdb.de]